Ultrastructure and Morphology of Compound Eyes of the Scorpionfly Panorpa dubia (Insecta: Mecoptera: Panorpidae). - Qing-Xiao Chen; Bao-Zhen Hua (PLoS ONE, 2016)
Mecoptera are unique in holometabolous insects in that their larvae have compound eyes. In the present study the cellular organisation and morphology of the compound eyes of adult individuals of the scorpionfly Panorpa dubia in Mecoptera were investigated by light, scanning electron, and transmission electron microscopy. The results showed that the compound eyes of adult P. dubia are of the apposition type, each eye comprising more than 1200 ommatidia. The ommatidium consists of a cornea, a crystalline cone made up of four cone cells, eight photoreceptors, two primary pigment cells, and 18 secondary pigment cells. The adult ommatidium has a fused rhabdom with eight photoreceptors. Seven photoreceptors extend from the proximal end of the crystalline cone to the basal matrix, whereas the eighth photoreceptor is shorter, extending from the middle level of the photoreceptor cluster to the basal matrix. The fused rhabdom is composed of the rhabdomeres of different photoreceptors at different levels. The adult ommatidia have the same cellular components as the larval ommatidia, but the tiering scheme is different.